2005
DOI: 10.22358/jafs/70582/2005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feed additives on nutrient digestibility and the bacterial status of faeces in pigs

Abstract: The effects of different feed additives (flavomycin, oregano, MOS and Lactobacillus plantarum) added to diets for growing pigs (20 kg BW) on nutrient digestibility and the microbial status of faeces were investigated in the study.Diet supplementation with different feed additives had no effect on the digestibility of most nutrients. Faecal bacterial populations (E. coli, Lactobacilli spp.) were not affected by diet composition. Diets supplemented with oregano, MOS and L. plantarum did not increase the activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
1
1
2
Order By: Relevance
“…A significantly lower digestibility coefficient of cellulose was observed in rabbits fed the diet supplemented with MOS. Similarly, a significantly lower digestibility coefficient of crude fibre was observed in the growing pigs fed a diet with MOS in comparison with control pigs (Lipiń ski et al, 2005). In our study, lower digestibility of cellulose can be explained by lower cellulolytic activity observed in the caecum of these rabbits (Table 5).…”
Section: Discussionsupporting
confidence: 69%
“…A significantly lower digestibility coefficient of cellulose was observed in rabbits fed the diet supplemented with MOS. Similarly, a significantly lower digestibility coefficient of crude fibre was observed in the growing pigs fed a diet with MOS in comparison with control pigs (Lipiń ski et al, 2005). In our study, lower digestibility of cellulose can be explained by lower cellulolytic activity observed in the caecum of these rabbits (Table 5).…”
Section: Discussionsupporting
confidence: 69%
“…In fact, Trocino et al (2013b), in a meta-study on soluble fibre in rabbits, showed that an increase in dietary SF is positively correlated with an improvement in the digestibility of the remaining fibrous fractions. However, contrary to expectations, other studies have observed a lower cellulose digestibility in rabbits (Volek et al, 2007) and pigs (Lipinski et al, 2005) when mannan-oligosaccharides were included in the diet. On the other hand, although the faecal digestibility of NDF and ADF increased with the age of growing rabbits, no interaction with FSG inclusion was observed.…”
Section: Discussioncontrasting
confidence: 81%
“…In fact, , in a meta-study on soluble fibre in rabbits, showed that an increase in dietary SF is positively correlated with an improvement of the digestibility of the remaining fibrous fractions. However, contrary to expectations, other studies have observed a lower cellulose digestibility in rabbits and pigs (Lipinski et al, 2005) when mannan-oligosaccharides were included in the diet. On the other hand, although the faecal digestibility of NDF and ADF increased with the age of growing rabbits, no interaction with FSG inclusion was observed.…”
Section: Discussioncontrasting
confidence: 81%
“…Accordingly, Gómez-Conde et al (2007) and ( 2009) reported that increasing dietary SF content may stimulate the growth of fibrolytic microbiota in the gut, thus increasing the utilisation at both ileum and caecum of insoluble fibre fractions (hemicelluloses and ADF). However, other feed ingredients such as MOS reduced cellulose digestibility when added in rabbits and pigs' diet, explained by a lower cellulotic activity observed in the caecum of those animals (Lipinski et al, 2005;. However, all the fibre fractions were decreased by the gradual inclusion of FSG from 0 to 20 g/kg in the SF diet already even in the in vitro enzymatic pre-digestion, (-1.6, -1.1, -0.92 g/kg for NDF, ADF and cellulose respectively for each g/kg of FSG added).…”
Section: Discussionmentioning
confidence: 97%